A low-Tc superconducting modification of Th4H15 synthesized under high pressure. (4th February 2021) - Wang, N N; Shan, P F; Chen, K Y; Sun, J P; Yang, P T; Ma, X L; Wang, B S; Yu, X H; Zhang, S; Chen, G F; Cheng, J-G; Dong, X L; et al.
Abstract: Among the metal hydrides, Th4 H15 is the first reported superconductor with a relatively high T c ≍ 8 K at ambient pressure. Here we report on the synthesis and characterization of a low- T c superconducting modification of Th4 H15, which is obtained via hydrogenating Th metal at 5 GPa and 800 °C by using the ammonia borane as the hydrogen source. Measurements of resistivity, magnetic susceptibility, and specific heat confirm that the obtained Th4 H15 sample shows a bulk superconducting transition at T c ≍ 6 K, which is about 2 K lower than that reported previously. Various characteristic superconducting parameters have been extracted for this compound and unusual lattice dynamics were evidenced from the specific-heat analysis.